2005
DOI: 10.1002/ijc.21596
|View full text |Cite
|
Sign up to set email alerts
|

Essential contribution of a chemokine, CCL3, and its receptor, CCR1, to hepatocellular carcinoma progression

Abstract: We previously observed that a chemokine, macrophage inflammatory protein-1 a/CCL3, and its receptor, CCR1, were aberrantly expressed in human hepatocellular carcinoma (HCC) tissues. Here, we show that CCL3 and CCR1 are also expressed in 2 different models of this cancer; N-nitrosodiethylamine (DEN)-induced HCC and HCC induced by hepatitis B virus surface (HBs) antigen-primed splenocyte transfer to myelo-ablated syngeneic HBs antigen transgenic mice. At 10 months after DEN treatment, foci number and sizes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 41 publications
4
75
0
Order By: Relevance
“…At 10 months after the injection, nodules consisting of highly dysplastic malignant cells were observed in liver of Pim-3 transgenic mice and to a lesser extent in WT mice (Figure 5a). Macroscopically, approximately half of male WT mice developed HCC nodules at 10 months after DEN injection , consistent with the previous report (Yang et al, 2006). In contrast, most Pim-3 transgenic mice developed HCC nodules by 10 months after DEN treatment, with higher relative liver weight and larger numbers of HCC nodules than WT mice (Figures 5b-e).…”
Section: Enhanced Hepatocarcinogenesis In Pim-3 Transgenic Micesupporting
confidence: 91%
See 1 more Smart Citation
“…At 10 months after the injection, nodules consisting of highly dysplastic malignant cells were observed in liver of Pim-3 transgenic mice and to a lesser extent in WT mice (Figure 5a). Macroscopically, approximately half of male WT mice developed HCC nodules at 10 months after DEN injection , consistent with the previous report (Yang et al, 2006). In contrast, most Pim-3 transgenic mice developed HCC nodules by 10 months after DEN treatment, with higher relative liver weight and larger numbers of HCC nodules than WT mice (Figures 5b-e).…”
Section: Enhanced Hepatocarcinogenesis In Pim-3 Transgenic Micesupporting
confidence: 91%
“…Chemical-induced liver injury and subsequent hepatocarcinogenesis Three-week old weaning mice were given a single intraperitoneal injection of DEN (Sigma-Aldrich), dissolved in physiological saline solution at a dose 10 mg/kg body weight as previously described (Yang et al, 2006), to induce hepatocarcinogenesis. To induce acute liver injury, mice were given a dose of 100 mg/kg body weight.…”
Section: Protein Extraction and Western Blottingmentioning
confidence: 99%
“…Our results show that the tumor-suppressive effects of NCoR are linked to the silencing of genes involved in metastatic spreading, whose expression has been associated with poor prognosis in cancer patients (39)(40)(41)(42)(43)(44). NCoR, together with HDAC3, the main enzyme responsible for the repressive activity of NCoR (45), binds to the promoters of several prometastatic genes, thereby inhibiting histone acetylation and repressing their transcription.…”
Section: Discussionmentioning
confidence: 92%
“…[14][15][16][17][18][19][20][21][22][23][24][25] We hypothesized that expression of CCR1 would be enhanced in the intestines and liver following allo-SCT and would correlate with the influx of donor leukocytes into these organs during the development of GVHD. RNA was isolated from the intestines and liver at weeks 1, 4, and 6 after transplantation, and mRNA expression of CCR1 was determined using the RPA.…”
Section: Results Mrna and Protein Expression Of Ccr1 Is Increased Folmentioning
confidence: 99%
“…[10][11][12] CCR1 is a chemokine receptor that is expressed on neutrophils, monocytes, and T lymphocytes and binds several chemokine ligands, including CCL5/RANTES (regulated on activation, normal T expressed and secreted), CCL3/Mip-1␣, and CCL4/Mip-1␤. 13 A role for CCR1 has been well characterized in several inflammatory conditions, such as arthritis, 14,15 chronic kidney disease, [16][17][18] immune-mediated hepatitis, 19 tumor angiogenesis, 20 ischemia-reperfusion injury, 21 sepsis, 22,23 and transplantation rejection. 24,25 We have recently shown that CCL5 contributes to the development of lung injury and survival following allo-SCT.…”
Section: Introductionmentioning
confidence: 99%